Nanostructure Conducting Oxide Based on Schottky Diode - Elsayed, I. A.; Fahmy, T.; El-Tantawy, Farid; Farooq, W. A.; Yakuphanoğlu, Fahrettin (Amer Scientific Publishers, 2014)
Novel Schottky photodiode based on Al/p-Si/Li0.3V2O5/Au thin films have been successfully fabricated by sol gel spin coating approach. The as-prepared films were characterized by X-ray diffraction (X-ray), Fourier transformed infrared spectroscopy (FTIR), energy dispersive X-ray spectroscopy (EDS) and atomic force microscopy (AFM). The diameters of Li0.3V2O5 nanosheets were found to be 7 nm. The current voltage characteristics of the diode were investigated under dark and various light intensity. It was observed that generated photocurrent of the diode depends on light intensity. The transient photocurrent measurements indicate that the Al/p-Si/Li0.3V2O5/Au diode was very sensitive to illumination. The capacitance decreases with increasing voltage due to a continuous distribution of the interface states. The simplicity of LVO structure of a photodiode sensor opens up the possibility for mass production of new classes of environmentally conscious electronics.
Keywords: Li Doped V2O5; Sol-Gel; Microstructure; Optical Properties; Photodiode